The innocents - Simon, Taryn; Neufeld, Peter; Scheck, Barry; Innocence Project; Exhibition touring internationally New York. P.S. 1 Contemporary Art Center; Exhibition New York. Umbrage editions and The Innocence Project (New York : Umbrage Editions, 2003)
This is a collection of photographs and interviews gathered from across the United States of people imprisoned for years before finally proving their innocence
boek
Keywords: Simon, Taryn